Patterns and predictors of elevated blood pressure and hypertension among primary school children in urban Kenya. Issue 12 (29th December 2022) - Gewa, Constance A.; Onyango, Agatha C.; Opiyo, Rose O.; Gittelsohn, Joel; Cheskin, Lawrence J.
Abstract : Objective: We examined the prevalence of elevated blood pressure (BP) and hypertension among 390 primary school children of different socioeconomic status (SES) in two urban settings in Kenya and explored the association between children's BP status and their sociodemographic characteristics, dietary behaviours and overweight/obesity status. Methods: Children's BP and anthropometric measurements were taken and parents, with the help of their children, completed questionnaires on the children's dietary behaviours. An average of three BP readings was used to calculate BP percentiles by age, sex and height. BMI-for-age z-scores, waist-circumference-to-height ratio and the sum of skinfold measures were calculated. We utilized prevalence ratio analysis to examine the association between BP and sociodemographic characteristics, dietary behaviours and overweight/obesity. Results: About 9% of the school children had elevated BP and 33% had stage 1 hypertension. Among overweight children, the proportion of children with elevated BP was 1.85-fold greater and the proportion of children with hypertension was 1.83-fold greater compared with children with healthy body weight. Similar patterns of significant associations were seen among obese children, children with central obesity and children with high total skinfold values. The proportion of children with hypertension was 1.42-fold greater among children with high frequency of consumption of chips/crisps compared with children with lower frequency of consumption. Conclusion: These results increase our understanding BP patterns and determinants among school children in Kenya and can help inform noncommunicable disease prevention efforts.